PENGENALAN KOSAKATA BAHASA INGGRIS “THINGS AROUND US” PADA ANAK SANTRI PANTI ASUHAN AISYIYAH LUWUK - Nurhaida Lakuana; Yusniati N. Sabata (PT. CASA CENDEKIA MEDIA, 2024)
English education as an international language is an important aspect in improving the quality of human resources, especially for children in orphanages who often have limited access to education in this language. The English vocabulary introduction program with the theme